Does Perceived Organizational Support Have a Moderating Effect on Whistleblowing Intentions? - Indriani, Mirna; Nadirsyah, Nadirsyah; Dinaroe, Dinaroe (2022 International Conference on Decision Aid Sciences and Applications (DASA), 2022)
The purpose of this research was to investigate the impact of Personal Cost (PC), Organizational Commitment (OC), and Perception of Organizational Support (POS) on Whistleblowing Intentions (WI). An online survey of 150 employees in the government sector in Aceh Province was used to obtain data and the Partial Least Square Structural Equation Model (PLS_SEM) was utilized to test the hypotheses. The findings indicated that the higher the personal cost, the less likely a person wanted to utilize whistleblowing as a technique to prevent fraud, even when there was a feeling of strong organizational support. This study did not indicate that organizational commitment affects whistleblowing intention. Nevertheless, the result did show that a sense of organizational support affected the link between organizational commitment and whistleblowing intention to fraud. This study demonstrated that the impression of organizational support was a mechanism that might influence a person's behavior when committing to action.